CANCELLATION OF LAND OWNERSHIP RIGHTS CERTIFICATE IMPLEMENTED BY THE LAND OFFICE OF BENGKULU CITY - Okta Orlando; Hamdani Ma'akir; Herawan Sauni (Bengkoelen Justice : Jurnal Ilmu Hukum, 2021)
This study aimed to determine the procedure implemented in the cancellation of land ownership certificates implemented by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency of Bengkulu Province, which was based on the Supreme Court Decision Number: 814K/PDT/2009 that has permanent legal force. The type of study used was juridical empirical legal research with descriptive characteristic, meaning that the research aimed to explain the procedure for the cancellation of a land ownership certificate by looking at the conformity between the applicable legal rules and those applied in the process of canceling a land ownership right. The approach applied in this study was qualitative, which is an analysis that describes the applicable regulations, then linked them to the cancellation of the certificate, the analysis was formed by words based on the technique of collecting and analyzing the relevant data obtained from the implementation of the procedure for cancellation of land ownership rights. While the populations in this study were the litigants and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency of Bengkulu Province. Primary data collection was carried out by using semi-structured interview technique. Then the primary and secondary data were analyzed by using qualitative descriptive analysis. The results of this study showed that the certificate cancellation had been in accordance with the applicable procedures. Suggestions that can be given were that the cancellation of the certificate of land ownership rights must fulfill all formal requirements in implementing the cancellation of land ownership rights.